2015
DOI: 10.1590/0103-8478cr20150295
|View full text |Cite
|
Sign up to set email alerts
|

Inducers and autoinducers on Salmonella enterica serovar Typhimurium motility, growth and gene expression

Abstract: Genus Salmonella bacteria are among the major pathogenic microorganisms in food. This bacterium pathogenicity is related to a number of virulence factors, among which its flagella.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Our results were comparable to Thung et al [ 55 ], who detected the Stn gene in 50% of S. typhimurium isolates recovered from beef samples [ 55 ]. Furthermore, the SdiA gene is involved in epithelial cell adhesion and biofilm development via quorum sensing [ 56 , 57 , 58 , 59 ]. The results obtained are consistent with Yin et al [ 60 ], who detected the SdiA gene in >75% of biofilm-producing S. typhimurium isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were comparable to Thung et al [ 55 ], who detected the Stn gene in 50% of S. typhimurium isolates recovered from beef samples [ 55 ]. Furthermore, the SdiA gene is involved in epithelial cell adhesion and biofilm development via quorum sensing [ 56 , 57 , 58 , 59 ]. The results obtained are consistent with Yin et al [ 60 ], who detected the SdiA gene in >75% of biofilm-producing S. typhimurium isolates.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that epinephrine plays an important role in stimulating motility in S. Typhimurium, so it seems that it is playing a key role in the mechanism of Quorum Sensing. This would trigger the activation of genes related to motility such as fliC owing to the fact that the presence of this neurotransmitter increases its expression 21 times (Conceição et al, 2015).…”
Section: Introductionmentioning
confidence: 99%